PREVENTIVE MEASURES - EXCEPTION TO THE PRINCIPLE OF THE RIGHT TO LIBERTY AND SECURITY - Marin-Alin DĂNILĂ (Challenges of the Knowledge Society)
Considering the specific obligations arising from the exercise of criminal action and civil action in criminal proceedings and taking into account the need to ensure a better conduct of activities that are undertaken in solving criminal cases, it sometimes appears necessary, taking certain procedural measures. Procedural measures were defined [1] as institutions available for criminal procedural law and criminal judicial bodies consisting of privations or certain constraints, real or personal, of the conditions and circumstances under which the criminal proceedings are being realized. By the function pursued by the legislature, these measures work as a legal means of prevention or suppression of circumstances or situations likely to jeopardize the effectiveness of the criminal proceedings through the obstacles, difficulties and confusion which they can produce [2]. Procedural measures arise as opportunities, but not being specific to any criminal case, judicial bodies take measures according to the specific circumstances of each criminal case. From this derives the adjacent character of the criminal procedural measures to the main job [3].